Powers of the committee of ministers of the council of europe in accordance with article 46 of the European convention on human rights - Аббакумова, Д. В. (Problems of legality, 2013)
This article is devoted to research the powers of the Committee of Ministers of the Council of Europe for supervision of the execution of judgments of the European Court of Human Rights. The author has analyzed the article 46 of the European Convention on Human Rights.